Perencanaan Strategis Pembangunan Kampung - MANA, FREDERIUKUS ANTONIUS MANA; Syahrabudin Husein Enala (PAPSEL Research and Consulting, 2025)
This study aims to analyze the strategic planning of Tof-Tof Village development in Eligobel District, Merauke Regency, using the SWOT analysis approach. The main problem studied is how an effective development strategy can be designed to optimize village potential, overcome internal weaknesses, and take advantage of opportunities and face external threats. This study uses a qualitative method with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study indicate that Tof-Tof Village has strengths in the form of potential natural resources and strong social cohesion, but faces weaknesses such as limited basic infrastructure and village apparatus capacity. Development opportunities come from the support of Papua's special autonomy policy and partnerships with external institutions, while threats include geographical isolation and dependence on external assistance. The conclusion of this study shows the need for participatory and adaptive strategic planning in facing the dynamics of sustainable village development.